(untitled) (Journal of Medical & Health Sciences Review, 2025)
Childhood diarrhea is a leading cause of morbidity and mortality among children under five, particularly in low- and middle-income countries like Pakistan. This study investigates the socio-demographic factors associated with the prevalence of diarrhea in children under five years of age in Peshawar, with the aim of identifying key determinants and providing evidence-based recommendations for targeted public health interventions. A cross-sectional study design was employed, involving 300 households selected through simple random sampling from urban and rural areas of Peshawar. Data were collected between January and June 2024 using a structured questionnaire covering socio-demographic characteristics, sanitation practices, healthcare access, and child health history. The data were analyzed using SPSS version 25, with descriptive statistics summarizing the study population and chi-square tests assessing associations between socio-demographic factors and diarrhea incidence. The findings revealed that children aged 1-3 years were most affected, with significant associations between diarrhea prevalence and maternal education, household income, family size, and sanitation practices. Poor hand hygiene, untreated water sources, and inadequate toilet facilities were identified as key risk factors. Despite the use of oral rehydration salts (ORS) and rotavirus vaccinations, gaps in awareness about diarrhea prevention persisted, highlighting the need for community education programs. This study underscores the critical role of socio-demographic and environmental factors in shaping the burden of childhood diarrhea in Peshawar. The results emphasize the importance of integrated strategies, including improved access to clean water and sanitation, parental education, and strengthened healthcare services, to reduce the incidence of diarrhea and improve child health outcomes. These findings provide valuable insights for policymakers and healthcare practitioners aiming to address this pressing public health issue.